PENGGUNAAN PUPUK UREA DAN PUPUK ORGANIK CAIR PADA PERTUMBUHAN DAN HASIL TANAMAN PADI - Gunawan, Sahrul; -, Widowati; Wisnubroto, Erwin Ismu (Prodi Agroteknologi Fakultas Agro Teknologi Universitas Prima Indonesia, 2024)
The utilization of urea compost and fluid natural manure (LOF) is extremely fundamental for rice plants. Urea contains high measures of nitrogen which can be consumed by plants rapidly and is significant for plant vegetative development. Fluid natural manure (LOF) gives more adjusted supplements to plants, particularly N, P and K. Fluid natural manure (LOF) likewise plays a part in further developing soil structure. This exploration means to concentrate on the impact of utilizing different dosages of urea compost and fluid natural manure (LOF) on the development and yield of rice plants. The examination will begin from October to December 2023 and will be done in the Science Techno Park garden at Tribhuwana Tunggadewi College. Non-factorial Randomized Block Configuration comprising of 4 medicines and 5 replications, each with urea manure portions of 0 kg/ha, 200 kg/ha, 400 kg/ha, and POC 100 cc/15 L of water. Plant level, wet and dry load of stover, and dry load of grain were the factors noticed. The examination of fluctuation test was utilized to investigate the perception information, trailed by the most un-massive distinction test (SRD 5%). The exploratory outcomes showed that the organization of different portions of urea compost and the utilization of LOF truly affected every noticed variable. The 400 kg/ha urea manure treatment gave the best grain dry weight (52.6 g/bunch). A urea portion of 200 kg/ha is comparable to the suggested utilization of POC in expanding stover weight and grain yield.